Alterations of the colour and of the degree of floculation of a Dark-Red Latosol under conditions of continuous cultivation of sugar cane - Prado, R. D.; Centurion, J. F. (Empresa Brasil Pesq Agropec, 2001)
The study aimed at assessing the degree of modification of certain physical properties and of the colour of the superficial soil layer of a Dark-Red Latosol of medium texture, subjected to the continuous cultivation of sugar cane during 25 years in Jaboticabal, SP, Brazil. The treatments consisted of two types of soil use, i.e. absence of cultivation (native vegetation) and intense cultivation with sugar cane, at three depth levels of 0-10, 10-20 and 20-30 cm. The continuous cultivation altered the colour of the level 0-10 cm from 2.5YR2.5/4 (absence of cultivation) to 2.5YR3/4, and impaired the macro structure and lessened the degree of flocculation of the soil's clay.
Keywords: Saccharum officinarum; soils; morphology; clay